1991
DOI: 10.1111/j.1471-4159.1991.tb08250.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human and Rat Ciliary Neurotrophic Factors

Abstract: The human ciliary neurotrophic factor (CNTF) gene was identified and cloned, based on homology with the recently cloned rat cDNA. The gene encodes a protein of 200 amino acids, which shares about 80% sequence identity with rat and rabbit CNTF and, like these homologues, lacks an apparent secretion signal sequence. The human CNTF gene, like the rat gene, appears to contain a single intron separating two protein coding exons. An intronless human CNTF gene was constructed by the use of polymerase chain reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 25 publications
(36 reference statements)
1
37
0
3
Order By: Relevance
“…The results obtained with this enriched preparation could later be confirmed by CNTF purified to homogeneity and recombinant CNTF (3,59,93,94).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 67%
See 1 more Smart Citation
“…The results obtained with this enriched preparation could later be confirmed by CNTF purified to homogeneity and recombinant CNTF (3,59,93,94).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 67%
“…That CNTF has a direct action on motoneurons could be deduced from the fact that the survival effect in single motoneuron cultures was identical to that in 80% pure low-density cultures (94) . The cloning of CNTF was the prerequisite for producing large quantities of recombinant CNTF (49,59,100) and for the determination of its developmental expression and cellular localization (20,27,86,94,97,100,101). These investigations demonstrated that CNTF is expressed postnatally in myelinating Schwann cells (27,86,97,100,101) and a subpopulation of type I astrocytes (20,101) in the CNS, that CNTF is a cytosolic molecule, and that the biological activity, e.g., in the adult sciatic nerve, is more than 10,000 _ times higher than that of (retrogradely) transported NGF in the rat sciatic nerve (35,97,98).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 99%
“…Cells were grown with 10% horse serum in Neurobasal medium supplemented with B27 and 500 mM glutamax I (Invitrogen, Eggensten, Germany) at 37°C in a humidified atmosphere with 5% CO 2 . After 1 h, the Neurobasal medium was supplemented with one of the following neurotrophic factors at a concentration of 1 ng/ml: glia-derived neurotrophic factor (GDNF) (PreProtech, Frankfurt, Germany); brain-derived neurotrophic factor (BDNF) (Amgen, Thousand Oaks, CA); and ciliary neurotrophic factor (CNTF) (rat and human expressed and purified as described by Masiakowski et al, 1991). The initial cell number per well was determined 3 h after plating by phase-contrast microscopy (magnification, 125ϫ).…”
Section: Methodsmentioning
confidence: 99%
“…Trophic Factors and Vincristine-Recombinant rat CNTF was prepared as described (26). HGF and vincristine were purchased from R&D Systems and Sigma, respectively.…”
Section: Methodsmentioning
confidence: 99%